Heart and brain: cortical representation of cardiac signals is disturbed in borderline personality disorder, but unaffected by oxytocin administration - Schmitz, Marius; Müller, Laura Elisa; Kleindienst, Nikolaus; Herpertz, Sabine; Bertsch, Katja (Journal of affective disorders, 2020)
Background - Emotional dysregulation, a core feature of borderline personality disorder (BPD) has recently been linked to deficits in the cortical representation of bodily signals. Oxytocin modulates the salience of external social cues. However, its role in interoception is still not fully understood. The aim of the current study was to replicate reduced heartbeat-evoked potentials (HEPs) as a marker for the cortical representation of cardiac signals in BPD and to explore potential effects of oxytocin on HEP amplitude. - Methods - Fifty-three medication-free women with a DSM-IV diagnosis of BPD and sixty healthy female controls (HCs) participated in the study. In a randomized, double-blind placebo-controlled trial, participants self-administered either 24 I.U. of oxytocin or placebo and took part in a 5-minute resting-state electrocardiogram (ECG) with parallel electroencephalogram (EEG) measurement. In addition, emotional dysregulation and BPD symptomatology were assessed with self-report questionnaires. - Results - Patients with BPD had significantly lower mean HEP amplitudes than HCs. Furthermore, HEP amplitudes were negatively correlated with emotional dysregulation in the whole sample. However, oxytocin had no significant effect on HEP amplitude. - Limitations - Only female participants were investigated and no clinicial controls were included. - Conclusions - This is the first replication from an independent sample showing a reduced cortical representation of cardiac signals in BPD patients. This, together with other body-related symptoms, suggests deficits in the processing of bodily signals, which seem to be associated with emotional dysregulation. Whether oxytocin influences HEP during emotion regulation tasks needs to be investigated in future studies.